Crisis Communication Strategies in Higher Education: A Mixed-Methods Investigation of Stakeholders Perceptions and Reputation - Dacosta, Stephanie Jean; Talili, Ismael (JPAIR Multidisciplinary Research, 2026)
This study investigates crisis communication in higher education through a mixed methods analysis of stakeholders’ perceptions and institutional reputation in the context of a 2021 virtual graduation technical failure crisis at the University of Science and Technology of Southern Philippines–Cagayan de Oro (USTP CDO). Guided by Situational Crisis Communication Theory (SCCT), the research examines how 105 stakeholders evaluated the perceived effectiveness of the university’s crisis communication response strategy, how they attributed responsibility for the crisis (victim, accidental, preventable), and how these factors shaped their perceptions of institutional reputation in terms of trust, integrity, and competence. Using convergent parallel mixed methods design centered on a single scenario based vignette of the virtual graduation platform failure, the study identifies key patterns in crisis perception, response evaluation, and reputational impact. Findings indicate that higher perceived communication effectiveness was associated with lower attribution of organizational responsibility and more favorable reputation scores, particularly on trust and integrity. Practical implications suggest that higher education institutions should adopt transparent, timely, and stakeholder centered communication strategies for virtual event crises, including pre testing technical systems, providing clear real time updates, and framing messages that reduce blame and rebuild confidence. Drawing on these results, the study proposes a preliminary stakeholder centered crisis communication framework for Philippine and regional higher education institutions.